Development of dansyl based copper(ii) complex to detect hydrogen sulfide in hypoxia. Issue 29 (10th July 2019) - Kim, Jee Young; Sarkar, Swarbhanu; Bobba, Kondapa Naidu; Huynh, Phuong Tu; Bhise, Abhinav; Yoo, Jeongsoo
Abstract : Hydrogen sulfide (H2 S) has been detected by fluorescence imaging in living cells under hypoxia. Abstract : Hydrogen sulfide (H2 S) has been reported as a gaseous signaling molecule in cells. H2 S modulation is dependent on the partial pressure of oxygen in cells, which means hypoxia can induce H2 S production under various pathophysiological conditions. Hypoxia is a common condition in solid tumors and can lead to malignant tumors that may become aggressive and result in worse prognosis. We designed and synthesized probeCu-CD for H2 S detection under hypoxia conditions. It is selective and sensitive toward various biological thiols, reactive nitrogen species (RNS), and reactive oxygen species (ROS). The fluorescence intensity ofCu-CD in the cytoplasms of HeLa and EMT6 cells was enhanced in proportion to the concentration of exogenous/endogenous H2 S. Moreover, Cu-CD can be able to detect endogenous H2 S production accompanied by expression of HIF-1α. Therefore, Cu-CD can be a key tool to explore how H2 S contributes to neovascularization and growth of solid tumor tissues in pathophysiological or hypoxic conditions.